AN ENHANCED STRAY FLUX APPROACH FOR ROTOR BAR FAULT DETECTION IN INDUCTION MACHINES (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This paper presents an enhanced method for detecting broken rotor bar (BRB) faults in squirrel-cage induction motors (SCIMs), with a focus on low- and no-load conditions. The approach relies on harmonic analysis of stray magnetic flux and is benchmarked against conventional Motor Current Signature Analysis (MCSA). Fault scenarios, including single and multiple broken bars in adjacent and non-adjacent configurations, are investigated using finite element simulations of a 2.2 kW motor. Results show that stray flux indicators provide higher sensitivity and accuracy than stator current–based methods. Experimental validation under varying load conditions (slip 0.049–0.092) confirms the effectiveness of the proposed approach, particularly under no-load operation. These findings highlight its suitability for real-time condition monitoring and predictive maintenance of SCIMs.
Keywords: Broken bars; Diagnostic; Finite element analysis; Induction motors; Modeling; Monitoring; Signal processing